Molecular epidemiology of rabies in northern South Africa and southern Zimbabwe demonstrates an epidemiological complexity that involves domestic dogs and jackals (Canis mesomelas) - Prof L H Nel (University of Pretoria, 2013)
Dissertation (MSc (Microbiology))--University of Pretoria, 2007.